Value of Free-Run Electromyographic Monitoring of Lower Cranial Nerves in Endoscopic Endonasal Approach to Skull Base Surgeries - Thirumala, Parthasarathy D.; Mohanraj, Santhosh Kumar; Habeych, Miguel; Wichman, Kelley; Chang, Yue-Fang; Gardner, Paul; Snyderman, Carl; Crammond, Donald J.; Balzer, Jeffrey (Journal of Neurological Surgery Part B: Skull Base, 2012)
Objective The main objective of this study was to evaluate the value of free-run electromyography (f-EMG) monitoring of cranial nerves (CNs) VII, IX, X, XI, and XII in skull base surgeries performed using endoscopic endonasal approach (EEA) to reduce iatrogenic CN deficits.Design We retrospectively identified 73 patients out of 990 patients who had EEA in our institution who had at least one CN monitored. In each CN group, we classified patients who had significant (SG) f-EMG activity as group I and those who did not as group II.Results We monitored a total of 342 CNs. A total of 62 nerves had SG f-EMG activity including CN VII = 18, CN IX = 16, CN X = 13, CN XI = 5, and CN XII = 10. No nerve deficit was found in the nerves that had significant activity during procedure. A total of five nerve deficits including (CN IX = 1, CN X = 2, CN XII = 2) were observed in the group that did not display SG f-EMG activity during surgery.Conclusions f-EMG seems highly sensitive to surgical manipulations and in locating CNs. It seems to have limited value in predicting postoperative neurological deficits. Future studies to evaluate the EMG of lower CNs during EEA procedures need to be done with both f-EMG and triggered EMG.
Keywords: electromyography; lower cranial nerves; endoscopic endonasal approach; skull base surgery